2012
DOI: 10.5507/bp.2012.045
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of women with high-risk pregnancies

Abstract: Aim. The aim of this study was to investigate the oral health status of women with high-risk pregnancies. Methods. A case-control study of 142 pregnant women was conducted. The case group included 81 pregnant women with high-risk pregnancies, while 61 women with normal pregnancies served as controls. The following variables were recorded for each woman: age, general health status, DMF, CPITN, and PBI index, amounts of Streptococcus mutans in the saliva and dental treatment needs. The Mann-Whitney test, Kruskal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
9
0
4
Order By: Relevance
“…Similar results were also seen in the study conducted by Karunachandra et al 8 in Sri Lanka; there they found that 92.5% of pregnant women had gingival or periodontal problems in urban area. Results of the study conducted by Pentapati et al, 9 Merglova et al, 10 Piscoya et al, 11 and Dhaliwal et al 12 also showed that gingival bleeding and periodontal pockets were significant problems reported by a large section of the expectant mothers. However, in the study conducted by Merglova et al, 10 only 9.8% of the pregnant women had periodontal pockets, whereas in the study conducted by Tilakaratne et al, 13 pregnancy had an effect only on the gingival and not on the periodontal attachment level.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similar results were also seen in the study conducted by Karunachandra et al 8 in Sri Lanka; there they found that 92.5% of pregnant women had gingival or periodontal problems in urban area. Results of the study conducted by Pentapati et al, 9 Merglova et al, 10 Piscoya et al, 11 and Dhaliwal et al 12 also showed that gingival bleeding and periodontal pockets were significant problems reported by a large section of the expectant mothers. However, in the study conducted by Merglova et al, 10 only 9.8% of the pregnant women had periodontal pockets, whereas in the study conducted by Tilakaratne et al, 13 pregnancy had an effect only on the gingival and not on the periodontal attachment level.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, in a study conducted by Pentapati et al, 9 the prevalence of dental caries was found to be 84% and mean DMFT was 4.08. Merglova et al 10 found the prevalence of dental caries to be 41.3%…”
Section: Discussionmentioning
confidence: 99%
“…Pain and gingival bleeding stimulates an increase of the gingival crevicular fluid volume. Moreover, increased tooth mobility is a clinical symptom of gestational effects on the periodontium (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Además, se ha evidenciado la disminución del pH salival, su función buffer y su potencial de remineralización en el embarazo en comparación con el postparto 10,11 , así como también la desvalorización de la atención que se presta a la salud oral 12,13 . No obstante y en independencia a la gravidez, se reconoce que factores socioculturales tales como la edad, raza, nivel de estudios y nivel profesional también pueden influir en la severidad de la enfermedad gingival 14 , sin embargo, no suelen ser tan importantes como lo son la higiene oral y el hábito tabáquico 5,14 .…”
Section: Introductionunclassified